2022
DOI: 10.1128/spectrum.02469-21
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights into bla GES Mobilome Reveal Extensive Genetic Variation in Hospital Effluents

Abstract: In the “One Health” approach, which encompasses human, animal, and environmental health, emerging issues of antimicrobial resistance are associated with hospital effluents that contain clinically relevant antibiotic-resistant bacteria along with a wide range of antibiotic concentrations, and lack regulatory status for mandatory prior and effective treatment. bla GES genes have been reported in aquatic environments despite the low detection of these genes among clinical isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 59 publications
2
11
0
Order By: Relevance
“…A study analyzing samples from hospital wastewater treatment plants identified bla GES as one of the dominant β-lactamase genes ( Hubeny et al, 2021 ). Indeed, GES-type carbapenemase producers have been identified in hospital wastewater samples from various countries ( Gomi et al, 2018 ; Suzuki Y. et al, 2020 ; Maehana et al, 2021 ; Conte et al, 2022 ; Takizawa et al, 2022 ; Zagui et al, 2023 ), which is consistent with our results. Additionally, bla GES -harboring isolates have been widely detected in wastewater treatment plants ( Girlich et al, 2012 ; Urase et al, 2022 ), suggesting that the resistance genes from sewage may also be disseminated into communities.…”
Section: Discussionsupporting
confidence: 93%
“…A study analyzing samples from hospital wastewater treatment plants identified bla GES as one of the dominant β-lactamase genes ( Hubeny et al, 2021 ). Indeed, GES-type carbapenemase producers have been identified in hospital wastewater samples from various countries ( Gomi et al, 2018 ; Suzuki Y. et al, 2020 ; Maehana et al, 2021 ; Conte et al, 2022 ; Takizawa et al, 2022 ; Zagui et al, 2023 ), which is consistent with our results. Additionally, bla GES -harboring isolates have been widely detected in wastewater treatment plants ( Girlich et al, 2012 ; Urase et al, 2022 ), suggesting that the resistance genes from sewage may also be disseminated into communities.…”
Section: Discussionsupporting
confidence: 93%
“…This region shared the highest nucleotide identity (≥99.98%) with the trb operon in 244kb and 49kb bla GES -encoding plasmids from A. caviae Aero21 and KAM329 respectively (Figure S1). A. caviae Aero21 was from hospital wastewater in Brazil [50] and KAM329 from an unknown source in Japan. The next most similar Aeromonas isolates had ≥ 97.65% sequence identity within the trb operon and were found on chromosomes from isolates ( Aeromonas sp.…”
Section: Resultsmentioning
confidence: 99%
“…This region shared the highest nucleotide identity (≥99.98%) with the trb operon in 244 kb and 49 kb bla GES -encoding plasmids from A. caviae Aero21 and KAM329, respectively ( Figure S1 ). A. caviae Aero21 was from hospital wastewater in Brazil [ 54 ] and KAM329 from an unknown source in Japan. The next most similar Aeromonas isolates had ≥97.65% sequence identity within the trb operon and were found on chromosomes from isolates ( Aeromonas sp.…”
Section: Resultsmentioning
confidence: 99%